Design and Implementation of Smart Car Driving - KulkarniS.D; Shendge P.S; Dixit P.K; Jadhav D.A (International Journal of Innovations in Engineering Research and Technology, 2021)
In this paperthe system used which consist of different types of sensors such as alcohol sensor, eye blink sensor, tiltsensor and also mainly used GSM modem, GPS receiver. The eye blink sensor is used to sense the person driving the vehicle is sleeping or not. Tilt sensor is used to identify weather the vehicle is running in normal condition or not when the accident occurs.it send the information to the controller system.The Alcohol Sensor is used to sense weather the person driving the car taken Alcohol or not and this data is also given to ADC